2018
DOI: 10.1097/hcr.0000000000000248
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the English Version of the HeartQoL Health-Related Quality of Life Questionnaire in Patients With Coronary Heart Disease

Abstract: The English HeartQoL health-related quality of life questionnaire is valid, reliable, and responsive in patients with angina and myocardial infarction allowing (1) assessment of baseline, (2) between-diagnosis comparisons, and (3) evaluation of change over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 27 publications
7
13
0
Order By: Relevance
“…The German HeartQoL demonstrated adequate convergent and divergent validity as well as internal consistency reliability in the total cohort and in each diagnosis. These results are similar to other studies using the HeartQoL, e.g., the English validation study including patients with angina or MI [27] which reported strong correlations with the respective matching physical and emotional scales of the HeartQoL and SF-36 (all coefficients r > .60). In the original HeartQoL study [19], Cronbach's alpha for the physical, emotional, and global scale was .90, .81, and .91, respectively, which was confirmed with the German HeartQoL version in this study.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The German HeartQoL demonstrated adequate convergent and divergent validity as well as internal consistency reliability in the total cohort and in each diagnosis. These results are similar to other studies using the HeartQoL, e.g., the English validation study including patients with angina or MI [27] which reported strong correlations with the respective matching physical and emotional scales of the HeartQoL and SF-36 (all coefficients r > .60). In the original HeartQoL study [19], Cronbach's alpha for the physical, emotional, and global scale was .90, .81, and .91, respectively, which was confirmed with the German HeartQoL version in this study.…”
Section: Discussionsupporting
confidence: 90%
“…Although there were no HeartQoL floor effects, high ceiling effects were observed on the emotional subscale in all groups with minimal effects on the physical and global scales. These observations, consistent with the original [19] and other validation studies [27][28][29][30][31], suggest that it may be more difficult to assess improvement in emotional HRQL than either physical or global HRQL with the HeartQoL questionnaire. Responsiveness was confirmed with significant pre-post HeartQoL physical, emotional, and global scale score changes with CR and with significant physical and global scale score changes after PCI.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…CHD patients were proven by clinic, electrocardiogram, and selective coronary arteriography according to the diagnostic criteria for CHD [ 22 , 23 ] and the standard questionnaire [ 24 ], and the patients aged more than 18 years.…”
Section: Methodsmentioning
confidence: 99%